Better Later Than Never: Meaning in Late Life - Pachana, Nancy A.; Baumeister, Roy F. (Frontiers in Psychology, 2021)
The quest for meaning in life takes on new challenges and directions during late life. This mini-review draws on prior theory to analyze meaningfulness into six discrete dimensions (purpose, value, efficacy, self-worth, mattering, and comprehension) and covers research into how these apply and operate specifically during late life. Limited remaining time, concern with one’s legacy, concerns with self-continuity and integration, variable challenges to self-worth, and prioritization of positivity emerge as key themes.